Emergency Department Visits Among Recipients of Chronic Opioid Therapy - Braden, Jennifer Brennan (2010)
BACKGROUND: There has been an increase in over dose deaths and emergency department visits (EDVs) involving use of prescription opioids, but the association between opioid prescribing and adverse outcomes is unclear. METHODS: Data were obtained from administrative claim records from Arkansas Medicaid and HealthCore commercially insured enrollees, 18 years and older, who used prescription opioids for at least 90 continuous days within a 6-month period between 2000 and 2005 and had no cancer diagnoses. Regression analysis was used to examine risk factors for EDVs and alcohol- or drug-related encounters (ADEs) in the 12 months following 90 days or more of prescribed opioids. RESULTS: Headache, back pain, and preexisting substance use disorders were significantly associated with EDVs and ADEs. Mental health disorders were associated with EDVs in HealthCore enrollees and with ADEs in both samples. Opioid dose per day was not consistently associated with EDVs but doubled the risk of ADEs at morphine-equivalent doses over 120 mg/d. Use of short-acting Drug Enforcement Agency Schedule II opioids was associated with EDVs compared with use of non–Schedule II opioids alone (relative risk range, 1.09–1.74). Use of Schedule II long-acting opioids was strongly associated with ADEs (relative risk range, 1.64–4.00). CONCLUSIONS: Use of Schedule II opioids, headache, back pain, and substance use disorders are associated with EDVs and ADEs among adults prescribed opioids for 90 days or more. It may be possible to increase the safety of chronic opioid therapy by minimizing the prescription of Schedule II opioids in these higher-risk recipients.